The NK-2 homeobox gene scarecrow (scro) is expressed in pharynx, ventral nerve cord and brain of Drosophila embryos. - Zaffran, S.; Das, G.; Frasch, M. (Mechanisms of Development, 2000)
Members of the NK homeobox family have been widely conserved during evolution. Here we describe the sequence and expression of a novel Drosophila NK-2 homeobox gene, named scarecrow (scro), which shows considerable homology to vertebrate Nkx-2.1. During embryogenesis, scro expression is initially observed in the pharyngeal primordia and later maintained in the pharynx. During band germ retraction, scro expression appears in two bilateral clusters of procephalic neuroblasts that give rise to distinct neuronal clusters in the brain. In addition, scro expression is observed in segmental clusters of neuronal precursors in the ventral nerve cord. In larval stages, scro expression occurs in portions of the optic lobe regions. These observations indicate that scro and vertebrate Nkx2.1 share similarities both in terms of their sequence and their expression patterns.